Influence of food additive – sunflower lecithin on the properties of dough for manufacturing bakery products - Shevchenko, Anastasiia; Drobot, Vira (My University, 2021)
The effect of lecithin on the gas-forming ability of the dough was determined. Samples of dough from high-grade flour with lecithin (3% by weight of flour) were prepared. Lecithin helps to improve the fertility of yeast due to its plastici-zation and the presence of choline, which has a positive effect on the condition of yeast cells. Analysis of the dynamics of gas formation showed the intensification of the released carbon dioxide in the sample with introduction of lecithin. Studies of the quantity and quality of gluten showed a decrease in the amount of raw and dry gluten. The addition of lecithin causes an increase in elasticity, reducing the dilution of the dough.
Keywords: lecithin; phospholipids; bakery product; dough; кафедра технології хлібопекарських і кондитерських виробів